Preparation method of easily-crosslinked polyacrylamide thickening agent

By using hydrolyzant outer layer coating and initiating polymerization technology in the thickener, a three-dimensional network structure that is resistant to temperature and salt resistant is formed, and the reservoir damage and cross-linking of existing thickeners in segmented fracturing is solved. The difficult problem improves the shear resistance of the thickener and the reservoir diversion ability.

CN119285823APending Publication Date: 2025-01-10DONGYING BAOMO ENVIRONMENT ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411615520.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing thickeners cause reservoir damage during the segmented fracturing process. Natural polymer thickeners have problems such as high water insoluble substances, many residues, difficult to control costs and poor biological stability. Synthesize polymer thickeners such as propylene Amide polymers have difficulty cross-linking, low strength of frozen glue, and poor shear resistance.

Method used

The outer layer of hydrolyzer sodium carbonate is coated, the pH value and concentration of acrylamide aqueous solution is adjusted, and the initiator is added to polymerize after nitrogen removal, forming a three-dimensional network structure, and the cross-linking rate is increased through uniform distribution of hydrolyzer to form a temperature resistance , salt-resistant and shear-resistant polyacrylamide thickener.

Benefits of technology

The crosslinking rate and frozen gel strength of polyacrylamide thickener are improved, the residue content is reduced, the process requirements of low permeability and ultra-low permeability reservoirs are met, and the diversion capacity of the reservoir and oil and gas well production capacity are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285823A_ABST
    Figure CN119285823A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thickening agents, and particularly relates to a preparation method of an easily-crosslinked polyacrylamide thickening agent, which comprises the following steps: (1) outer layer coating of a hydrolytic agent sodium carbonate, (2) liquid preparation of an acrylamide aqueous solution, (3) nitrogen introduction and oxygen removal of the acrylamide aqueous solution, (4) initiation polymerization of the acrylamide aqueous solution, and (5) hydrolysis of a polyacrylamide gel block. And (6) powdering and detecting the polyacrylamide. By adding the hydrolytic agent with the coating film, the polymerized polyacrylamide is uniformly hydrolyzed, carboxylate radicals are uniformly distributed, the probability of cross-linking among polyacrylamide molecules is greatly increased, and a temperature-resistant, salt-resistant and shear-resistant three-dimensional network structure is formed by cross-linking. The product quality indexes are as follows: the solid content is 89-91%, the molecular weight is greater than or equal to 2,000,000, the anion degree is 10-20%, the crosslinking rheological viscosity is greater than 150 centipoises, the crosslinking can be hung, and the requirements of low-permeability and ultra-low-permeability reservoirs and compact oil and gas reservoirs on the thickening agent are completely met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thickeners, and in particular relates to a method for preparing an easily cross-linked polyacrylamide thickener. Background Art

[0002] With the continuous deepening of oil field exploration, the proportion of low permeability, ultra-low permeability reservoirs and tight oil and gas reservoirs has gradually increased. Staged fracturing, as the most effective production increase measure for the above reservoirs, has received widespread attention. In the process of staged fracturing, the thickener used is an important component of the fracturing fluid. The thickener is a polymer compound that swells and dissolves in water, cross-links with the cross-linking agent, and greatly increases the viscosity of the system, thereby enhancing its sand carrying capacity. According to the source, the thickener can be divided into two categories: natural polymer thickener and synthetic polymer thickener.

[0003] Natural polymer thickeners are mainly natural plant gums such as guar gum, which have the advantages of simple preparation process and easy chemical cross-linking. However, since natural polymer thickeners contain 6% to 8% water-insoluble matter, the water-based fracturing fluid is not completely broken, resulting in a large amount of residues retained in the formation, causing damage to the formation and seriously affecting the transformation effect of the reservoir. The content of water-insoluble matter in the thickener is closely related to the residue content. The higher the content of water-insoluble matter, the higher the residue content. High thickener residue content will seriously affect the conductivity of the support fracture, forming a thick and dense filter cake on the fracture wall, hindering the output of formation fluids, causing reservoir damage and affecting the production capacity of oil and gas wells. Statistical data show that the average damage rate of water-based fracturing fluid to reservoir permeability is 30% to 45%, with a maximum of more than 60%, and the damage to the fracture support zone is more than 70%. At the same time, natural polymer thickeners also have problems such as difficult cost control and poor biological stability, making it difficult to promote on a large scale.

[0004] Synthetic polymer thickeners are mainly acrylamide polymers, which are one of the most widely used water-soluble polymers. Water-soluble polyacrylamide products include four series: anionic polyacrylamide, cationic polyacrylamide, zwitterionic polyacrylamide, and non-ionic polyacrylamide. They can be used as efficient flocculants, thickeners, coating agents, enhancers, dispersants, and fluid drag reducers, etc. They are widely used in water treatment, papermaking, petroleum, coal, mining and metallurgy, textiles, construction and other industrial sectors. They have broad development and utilization value and are high-tech products with development prospects.

[0005] The molecular structure of acrylamide polymers contains a large number of hydrophilic groups, which can bind to water molecules through hydrogen bonds. In addition, in aqueous solution, they can form complex structures through entanglement between molecular chains and intramolecular or intermolecular hydrogen bonds, which makes them have good thickening properties. The gel formed by acrylamide polymer thickeners has the characteristics of good viscoelasticity, good gel breaking performance and less residue. However, due to the uneven dispersion of carboxylate (COO-) in the molecular structure of acrylamide polymer ([CH2CH(CONH2)]m[CH2CH(COO-)]n), when acrylamide polymer undergoes chemical crosslinking with a crosslinking agent, the probability of crosslinking within the polyacrylamide molecule is greatly increased, and the probability of crosslinking between polyacrylamide molecules is greatly reduced, making it difficult to form a three-dimensional network structure, resulting in defects such as difficulty in chemical crosslinking between polyacrylamide molecules, low gel strength, poor shear resistance, and poor temperature and salt resistance. If the alkaline hydrolyzing agent sodium carbonate is added before polymerization, it will be difficult to adjust the pH value of the acrylamide aqueous solution, making it difficult for acrylamide containing an inhibitor to initiate polymerization. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing an easily cross-linked polyacrylamide thickener in view of the above-mentioned defects in the prior art.

[0007] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing an easily cross-linked polyacrylamide thickener, comprising the following steps:

[0008] (1) Outer coating of hydrolyzing agent sodium carbonate:

[0009] Mix polyoxyethylene sorbitol beeswax derivative and oleth-20, heat to 45-50°C, spray on the outer layer of the hydrolyzing agent sodium carbonate, cool to room temperature, and form a protective film on the outer layer of the sodium carbonate;

[0010] (2) Preparation of acrylamide aqueous solution:

[0011] The concentration of the aqueous acrylamide solution containing less than 50 ppm of polymerization inhibitor is adjusted to 18-22 wt %, the pH value is adjusted to 6.5-8.5, and the temperature is adjusted to 0° C.-5° C.;

[0012] (3) Nitrogen deoxygenation of acrylamide aqueous solution:

[0013] The acrylamide aqueous solution in step (2) is placed in a thermos bottle and deoxygenated by nitrogen for 40 to 60 minutes;

[0014] (4) Initiation of polymerization of acrylamide aqueous solution:

[0015] The hydrolyzing agent sodium carbonate coated with an outer film in step (1) is added to the acrylamide aqueous solution after nitrogen flow and deoxygenation, and then a chain transfer agent methanol, an oxidizing agent potassium chlorate aqueous solution with a concentration of 1.0 to 5.0 wt % and a reducing agent sodium thiosulfate aqueous solution with a concentration of 0.2 to 0.5 wt % are added in sequence to initiate polymerization until the temperature stops rising, and the polymerization is completed to obtain an acrylamide rubber block;

[0016] (5) Hydrolysis of polyacrylamide gel block:

[0017] The polymerized acrylamide block is taken out from the thermos, cut into long strips with scissors, and packed in a plastic bag. The plastic bag is placed in a constant temperature water bath at 80℃ to 95℃ for heating and hydrolysis reaction for 4 to 6 hours. At this temperature, the hydrolyzing agent penetrates the outer membrane and reacts with the polyacrylamide for hydrolysis.

[0018] (6) Powdering and testing of polyacrylamide:

[0019] After the hydrolysis of polyacrylamide is completed, granulation and drying are carried out, and the drying temperature is controlled at 55-65°C. The powder is ground into fine powder with a particle size of 150-80 mesh. The solid content, molecular weight and ionicity index of the acrylamide polymer are tested. The fine powder is dissolved in water and cross-linked with the cross-linking agent organic zirconium. The hanging performance and rheological viscosity of the cross-linked jelly are tested.

[0020] Furthermore, in the step (1), the mass ratio of the polyoxyethylene sorbitol beeswax derivative to oleth-20 is 5:1-10; and the mass ratio of sodium carbonate to the mixture of the polyoxyethylene sorbitol beeswax derivative and oleth-20 is 2:1-3:1.

[0021] Furthermore, in the step (3), the purity of the nitrogen gas passed through is ≥99.95%, and the nitrogen flow rate is controlled at 6-8 L / min.

[0022] Furthermore, in the step (4), the mass ratio of the hydrolyzing agent sodium carbonate covered with an outer membrane to the acrylamide aqueous solution after nitrogen deoxygenation is 1:30 to 1:50; the mass (percentage) ratio of the chain transfer agent methanol to acrylamide is 1:50 to 1:500; the mass (percentage) ratio of the added oxidizing agent potassium chlorate to the mass (percentage) ratio of acrylamide is 1:1000 to 1:10000; the mass (percentage) ratio of the added reducing agent sodium thiosulfate to the mass (percentage) ratio of acrylamide is 1:10000 to 1:50000.

[0023] The chemical name of Oleth-20 is polyoxyethylene (20) oleyl ether, the INCI name is Oleth-20 or Oleth-20, and the CAS number is 9004-98-2.

[0024] The surface layer of the hydrolyzing agent in the present invention is coated with a coating agent, which is evenly dispersed in the acrylamide aqueous solution, but not dissolved therein, so that the pH value of the acrylamide aqueous solution can be adjusted. According to the content of the polymerization inhibitor such as p-hydroxyanisole in the acrylamide aqueous solution, the pH value of the acrylamide aqueous solution is adjusted, so that the acrylamide polymerization rate is not affected by the content of the polymerization inhibitor. The acrylamide aqueous solution is deoxygenated by nitrogen, an initiator is applied, polymerization is initiated, and after the acrylamide is polymerized to form a block, the hydrolyzing agent is evenly distributed in the polyacrylamide block, the polyacrylamide block is heated and hydrolyzed, and during the heating process, the coating agent on the surface of the hydrolyzing agent melts and falls off, and the hydrolyzing agent and the polyacrylamide are contact-hydrolyzed to generate anionic polyacrylamide with evenly distributed carboxylate radicals, and the amount of the hydrolyzing agent is controlled, so that the generated anionic polyacrylamide is convenient for intermolecular crosslinking, and the crosslinking forms a three-dimensional network structure, which is heat-resistant, salt-resistant, and shear-resistant, and exhibits excellent thickening ability, and the shear rate is 100s. -1 , the rheological viscosity can be as high as 100 centipoise under the detection temperature of 140℃.

[0025] The invention has the following beneficial effects: by adding a hydrolyzing agent with a coating film before polymerization, the invention solves the problem that the pH value of acrylamide aqueous solution is difficult to adjust by adding an alkaline hydrolyzing agent sodium carbonate before polymerization, which makes it difficult for acrylamide containing a polymerization inhibitor to initiate polymerization, makes acrylamide polymerization simple and feasible, overcomes the problem of uneven addition of a hydrolyzing agent after polymerization, makes polyacrylamide hydrolyzed uniformly after polymerization, and distributes carboxyl groups uniformly, avoids the prominent aggregation of carboxyl groups, reduces the possibility of cross-linking within polyacrylamide molecules, greatly increases the probability of cross-linking between polyacrylamide molecules, and cross-linking forms a three-dimensional network structure that is resistant to heat, salt, and shear. The quality indicators of the polyacrylamide thickener product manufactured by the invention are: solid content: 89-91%, molecular weight: ≥21 million, anionicity: 10-20%, cross-linking rheological viscosity greater than 150 centipoise, cross-linking can be hung, and fully meets the process requirements of low permeability, ultra-low permeability reservoirs, and dense oil and gas reservoirs for thickeners. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a hanging photo of the anionic polyacrylamide thickener prepared in Example 1 of the present invention.

[0027] Figure 2 is the rheological viscosity of the anionic polyacrylamide thickener prepared in Example 1 of the present invention.

[0028] Figure 3 This is a hanging photo of the anionic polyacrylamide thickener prepared in Example 2 of the present invention.

[0029] Figure 4 It is the rheological viscosity of the anionic polyacrylamide thickener prepared in Example 2 of the present invention.

[0030] Figure 5 This is a hanging photo of the anionic polyacrylamide thickener prepared in Example 3 of the present invention.

[0031] Figure 6 It is the rheological viscosity of the anionic polyacrylamide thickener prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0032] The following are specific embodiments of the present invention, which further describe the technical solution of the present invention, but the protection scope of the present invention is not limited to these embodiments. Any changes or equivalent substitutions that do not deviate from the concept of the present invention are included in the protection scope of the present invention.

[0033] Example 1

[0034] (1) Weigh 5 g of polyoxyethylene sorbitol beeswax derivative and 1 g of oleth-20, mix and heat to 45° C., spray on the outer layer of 12 g of sodium carbonate, and cool to room temperature so that the outer layer of the sodium carbonate is covered with a uniform outer film.

[0035] (2) Add 210 g (100%) of an aqueous solution of acrylamide having an inhibitor content of 45 ppm and a concentration of 22% to a 2000 mL beaker, add deionized water, adjust the concentration of acrylamide to 21 wt %, place in an ice water bath, slowly add about 0.1 g of sodium carbonate to adjust the pH to 6.5, and the temperature to 2° C. to obtain an aqueous solution of acrylamide having a concentration of 21 wt %.

[0036] (3) Pour the acrylamide aqueous solution in step (2) into a 2 L thermos bottle, and pass nitrogen to deoxygenate for 40 min. The nitrogen purity is ≥99.95%, and the nitrogen flow rate is controlled at 6-8 L / min.

[0037] (4) adding the sodium carbonate coated with an outer membrane in step (1) to the acrylamide aqueous solution deoxygenated by nitrogen, and then sequentially adding methanol, a 1.0 wt% potassium chlorate aqueous solution and a 0.2 wt% sodium thiosulfate aqueous solution, continuing to pass nitrogen for 10 minutes, stopping nitrogen passing, plugging a thermos bottle with a thermometer, initiating polymerization, and completing polymerization until the temperature does not rise. The mass ratio of the hydrolyzing agent sodium carbonate coated with an outer membrane to the acrylamide aqueous solution deoxygenated by nitrogen is 1:40; the mass ratio of the chain transfer agent methanol to the acrylamide is 1:50; the mass ratio of the added mass of the oxidizing agent potassium chlorate to the mass ratio of the acrylamide is 1:10000; the mass ratio of the added mass of the reducing agent sodium thiosulfate to the mass ratio of the acrylamide is 1:10000.

[0038] (5) Break the thermos flask, take out the polymerized polyacrylamide block, cut it into long strips with scissors, and pack it in a plastic bag. Place the plastic bag containing the polyacrylamide block in a constant temperature water bath at 85°C and heat it for 5 hours. At this temperature, sodium carbonate penetrates the outer membrane and reacts with polyacrylamide to hydrolyze it.

[0039] (6) After the hydrolysis of polyacrylamide is completed, the rubber block is made into particles with a particle size of 2 to 5 mm by a granulator, and the particles are placed in an oven at a temperature of 55°C and dried with air for 45 minutes. The dried particles are taken out and crushed into fine powder with a particle size of 150 mesh to 80 mesh by a pulverizer. In this way, a solid content of 90%, a molecular weight of 22 million, an anionic degree of 10%, a cross-linked rheological viscosity ≥ 190 centipoise, and a selectable anionic polyacrylamide thickener (such as Figure 1 , Figure 2 shown).

[0040] Example 2

[0041] (1) Weigh 6 g of polyoxyethylene sorbitol beeswax derivative and 1 g of oleth-20, mix and heat to 47° C., spray on the outer layer of 21 g of sodium carbonate, and cool to room temperature so that the outer layer of the sodium carbonate is covered with a uniform outer film.

[0042] (2) Add 210 g (100%) of an aqueous solution of acrylamide having an inhibitor content of 30 ppm and a concentration of 25% to a 2000 mL beaker, add deionized water, adjust the concentration of acrylamide to 22 wt %, place in an ice water bath, slowly add about 0.4 g of sodium carbonate to adjust the pH to 7.70, and the temperature to 0° C. to obtain an aqueous solution of acrylamide having a concentration of 22 wt %.

[0043] (3) Pour the acrylamide aqueous solution in step (2) into a 2L thermos bottle and pass nitrogen to deoxygenate for 50 minutes. The nitrogen purity is ≥99.95% and the nitrogen flow rate is controlled at 6-8L / min.

[0044] (4) adding the sodium carbonate coated with an outer membrane in step (1) to the acrylamide aqueous solution deoxygenated by nitrogen, and then sequentially adding methanol, a 3.0wt% potassium chlorate aqueous solution and a 0.4wt% sodium thiosulfate aqueous solution, continuing to pass nitrogen for 10 minutes, stopping nitrogen passing, plugging a thermos bottle with a thermometer, initiating polymerization, and completing polymerization until the temperature does not rise. The mass ratio of the hydrolyzing agent sodium carbonate coated with an outer membrane to the acrylamide aqueous solution deoxygenated by nitrogen is 1:30; the mass ratio of the chain transfer agent methanol to the acrylamide is 1:500; the mass ratio of the added mass of the oxidizing agent potassium chlorate to the mass ratio of the acrylamide is 1:5000; the mass ratio of the added mass of the reducing agent sodium thiosulfate to the mass ratio of the acrylamide is 1:30000.

[0045] (5) Break the thermos flask, take out the polymerized polyacrylamide block, cut it into long strips with scissors, and pack it in a plastic bag. Place the plastic bag containing the polyacrylamide block in a constant temperature water bath at 80°C and heat it for 6 hours. At this temperature, sodium carbonate penetrates the outer membrane and reacts with polyacrylamide to hydrolyze it.

[0046] (6) After the hydrolysis of polyacrylamide is completed, the rubber block is made into particles with a particle size of 2 to 5 mm by a granulator, and the particles are placed in an oven at a temperature of 62°C and dried by blowing air for 45 minutes. The dried particles are taken out and crushed into fine powder with a particle size of 150 mesh to 80 mesh by a pulverizer. In this way, a solid content of 91%, a molecular weight of 22.5 million, an anionic degree of 11%, a cross-linking rheological viscosity of ≥180 centipoise, and an anionic polyacrylamide thickener (such as Figure 3 , Figure 4 shown).

[0047] Example 3

[0048] (1) Weigh 10 g of polyoxyethylene sorbitol beeswax derivative and 1 g of oleth-20, mix and heat to 50° C., spray on the outer layer of 24 g of sodium carbonate, and cool to room temperature so that the outer layer of the sodium carbonate is covered with a uniform outer film.

[0049] (2) Add 210 g (100%) of an aqueous solution of acrylamide having an inhibitor content of 10 ppm and a concentration of 25% to a 2000 mL beaker, add deionized water, adjust the concentration of acrylamide to 18 wt %, place in an ice water bath, slowly add about 0.6 g of sodium carbonate to adjust the pH to 8.50, and the temperature to 5° C. to obtain an aqueous solution of acrylamide having a concentration of 18 wt %.

[0050] (3) Pour the acrylamide aqueous solution in step (2) into a 2L thermos bottle, and pass nitrogen to deoxygenate for 60 minutes. The nitrogen purity is ≥99.95%, and the nitrogen flow rate is controlled at 6-8L / min.

[0051] (4) adding the sodium carbonate coated with an outer membrane in step (1) to the acrylamide aqueous solution deoxygenated by nitrogen, and then sequentially adding methanol, a 5.0wt% potassium chlorate aqueous solution and a 0.5wt% sodium thiosulfate aqueous solution, continuing to pass nitrogen for 10 minutes, stopping nitrogen passing, plugging a thermos bottle with a thermometer, initiating polymerization, and completing polymerization until the temperature does not rise. The mass ratio of the hydrolyzing agent sodium carbonate coated with an outer membrane to the acrylamide aqueous solution deoxygenated by nitrogen is 1:50; the mass ratio of the chain transfer agent methanol to the acrylamide is 1:200; the mass ratio of the added mass of the oxidizing agent potassium chlorate to the mass ratio of the acrylamide is 1:1000; the mass ratio of the added mass of the reducing agent sodium thiosulfate to the mass ratio of the acrylamide is 1:50000.

[0052] (5) Break the thermos flask, take out the polymerized polyacrylamide block, cut it into long strips with scissors, and pack it in a plastic bag. Place the plastic bag containing the polyacrylamide block in a constant temperature water bath at 95°C and heat it for 4 hours. At this temperature, sodium carbonate penetrates the outer membrane and reacts with polyacrylamide to hydrolyze it.

[0053] (6) After the hydrolysis of polyacrylamide is completed, the rubber block is made into particles with a particle size of 2 to 5 mm by a granulator, and the particles are placed in an oven at a temperature of 65°C and dried by blowing air for 40 minutes. The dried particles are taken out and crushed into fine powder with a particle size of 150 mesh to 80 mesh by a pulverizer. In this way, a solid content of 91%, a molecular weight of 23.5 million, an anionic degree of 12%, a cross-linked rheological viscosity of ≥225 centipoise, and a selectable anionic polyacrylamide thickener (such as Figure 5 , Figure 6 shown).

[0054] The present invention is not limited to the above-mentioned implementation modes, and anyone should be aware of the structural changes made under the enlightenment of the present invention, and all those having the same or similar technical solutions as the present invention fall within the protection scope of the present invention.

[0055] The techniques, shapes, and structural parts not described in detail in the present invention are all well-known techniques.

Claims

1. A method for preparing a cross-linkable polyacrylamide thickener, characterized in that: The following steps are involved: (1) Outer coating of hydrolyzing agent sodium carbonate: Mix polyoxyethylene sorbitol beeswax derivative and oleth-20, heat to 45-50°C, spray on the outer layer of the hydrolyzing agent sodium carbonate, cool to room temperature, and form a protective film on the outer layer of the sodium carbonate; (2) Preparation of acrylamide aqueous solution: The concentration of the aqueous acrylamide solution containing less than 50 ppm of polymerization inhibitor is adjusted to 18-22 wt %, the pH value is adjusted to 6.5-8.5, and the temperature is adjusted to 0° C.-5° C.; (3) Nitrogen deoxygenation of acrylamide aqueous solution: The acrylamide aqueous solution in step (2) is placed in a thermos bottle and deoxygenated by nitrogen for 40 to 60 minutes; (4) Initiation of polymerization of acrylamide aqueous solution: The hydrolyzing agent sodium carbonate coated with an outer film in step (1) is added to the acrylamide aqueous solution after nitrogen flow and deoxygenation, and then a chain transfer agent methanol, an oxidizing agent potassium chlorate aqueous solution with a concentration of 1.0 to 5.0 wt % and a reducing agent sodium thiosulfate aqueous solution with a concentration of 0.2 to 0.5 wt % are added in sequence to initiate polymerization until the temperature stops rising, and the polymerization is completed to obtain an acrylamide rubber block; (5) Hydrolysis of polyacrylamide gel block: The polymerized acrylamide block is taken out from the thermos, cut into long strips with scissors, and packed in a plastic bag. The plastic bag is placed in a constant temperature water bath at 80℃ to 95℃ for heating and hydrolysis reaction for 4 to 6 hours. At this temperature, the hydrolyzing agent penetrates the outer membrane and reacts with the polyacrylamide for hydrolysis. (6) Powdering and testing of polyacrylamide: After the hydrolysis of polyacrylamide is completed, granulation and drying are carried out, and the drying temperature is controlled at 55-65°C. The powder is ground into fine powder with a particle size of 150-80 mesh. The solid content, molecular weight and ionicity index of the acrylamide polymer are tested. The fine powder is dissolved in water and cross-linked with the cross-linking agent organic zirconium. The hanging performance and rheological viscosity of the cross-linked jelly are tested.

2. The method for preparing the easily cross-linked polyacrylamide thickener according to claim 1, characterized in that: In the step (1), the mass ratio of the polyoxyethylene sorbitol beeswax derivative to oleth-20 is 5:1 to 10:1; the mass ratio of sodium carbonate to the mixture of the polyoxyethylene sorbitol beeswax derivative and oleth-20 is 2:1 to 3:

1.

3. The method for preparing the easily cross-linked polyacrylamide thickener according to claim 1, characterized in that: The purity of the nitrogen gas passed through in step (3) is ≥99.95%, and the nitrogen flow rate is controlled at 6-8 L / min.

4. The method for preparing the easily cross-linked polyacrylamide thickener according to claim 1, characterized in that: In the step (4), the mass ratio of the hydrolyzing agent sodium carbonate covered with an outer membrane to the acrylamide aqueous solution after nitrogen deoxygenation is 1:30 to 1:50; the mass ratio of the chain transfer agent methanol to acrylamide is 1:50 to 1:500; the mass ratio of the added mass of the oxidizing agent potassium chlorate to the mass ratio of acrylamide is 1:1000 to 1:10000; and the mass ratio of the added mass of the reducing agent sodium thiosulfate to the mass ratio of acrylamide is 1:10000 to 1:50000.